2018
DOI: 10.1038/s41591-018-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of oxidative phosphorylation exploits cancer vulnerability

Abstract: Metabolic reprograming is an emerging hallmark of tumor biology and an actively pursued opportunity in discovery of oncology drugs. Extensive efforts have focused on therapeutic targeting of glycolysis, whereas drugging mitochondrial oxidative phosphorylation (OXPHOS) has remained largely unexplored, partly owing to an incomplete understanding of tumor contexts in which OXPHOS is essential. Here, we report the discovery of IACS-010759, a clinical-grade small-molecule inhibitor of complex I of the mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
722
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 677 publications
(760 citation statements)
references
References 54 publications
37
722
1
Order By: Relevance
“…Our result suggests that glutamine deprivation sensitizes for LXR activation‐driven cell death (Appendix Fig ). Considering the levels of essential and non‐essential amino acids, we found that especially aspartate levels were suppressed, which is in keeping with earlier reports, demonstrating that under conditions of inhibition with OXPHOS, aspartate becomes critical for tumors to survive and grow (Appendix Fig ; Molina et al , ). Overall, these findings are consistent with a profound reprogramming of the TCA cycle reactions by LXR agonists.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our result suggests that glutamine deprivation sensitizes for LXR activation‐driven cell death (Appendix Fig ). Considering the levels of essential and non‐essential amino acids, we found that especially aspartate levels were suppressed, which is in keeping with earlier reports, demonstrating that under conditions of inhibition with OXPHOS, aspartate becomes critical for tumors to survive and grow (Appendix Fig ; Molina et al , ). Overall, these findings are consistent with a profound reprogramming of the TCA cycle reactions by LXR agonists.…”
Section: Resultssupporting
confidence: 91%
“…In agreement, the TCA cycle metabolites were altered and carbon tracing experiments showed decreased labeling by glucose‐derived carbons. We noted a decrease in labeling of the amino acid aspartate and nucleotides by glucose carbons, which is line with prior studies, that inhibition of OXPHOS depletes both aspartate and nucleotides, which in turn can elicit the induction of a potential DNA‐stress response (Molina et al , ). Through our glutamine tracing experiment, we have found that LXR activation renders tumor cells partially more dependent on glutamine for their survival.…”
Section: Discussionsupporting
confidence: 91%
“…Several compounds block complex I (official name: NADH:ubiquinone oxidoreductase) with high affinity: BAY87‐2243, IACS‐010759, and ME‐344 . The growth‐inhibitory effects of BAY87‐2243 and IACS‐010759 are abolished in human cancer cells manipulated to express a yeast enzyme that bypasses complex I (the NDI1 NADH‐ Q ‐oxidoreductase that does not translocate protons and, in yeast mitochondria, substitutes the role of complex I), supporting the idea that they specifically act on target . Some of these inhibitors have been introduced into phase I trials, yielding signs of toxicity for BAY87‐2243 (which caused grade III nausea/vomiting, http://ClinicalTrials.gov NCT01297530) (Table ) and no signal of clinical efficacy for ME‐344 .…”
Section: Strategies For Oxphos Inhibitionmentioning
confidence: 92%
“…Several compounds block complex I (official name: NADH: ubiquinone oxidoreductase) with high affinity: BAY87-2243, 42 IACS-010759, 14,43 and ME-344. 22 The growth-inhibitory effects of BAY87-2243 and IACS-010759 are abolished in human cancer cells manipulated to express a yeast enzyme that bypasses complex I (the NDI1 NADH-Q-oxidoreductase that does not translocate protons and, in yeast mitochondria, substitutes the role of complex I), supporting the idea that they specifically act on target.…”
Section: Strategies For Oxphos Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation